2007
DOI: 10.1007/s00432-007-0307-9
|View full text |Cite
|
Sign up to set email alerts
|

Large proportion of low frequency microsatellite-instability and loss of heterozygosity in pheochromocytoma and endocrine tumors detected with an extended marker panel

Abstract: The extended microsatellite panel is qualified to detect MSI in PCC. Nine percent of MSI-positive cases would have not been noticed by the use of the reference panel alone. PCCs are characterized by low frequency MSI pointing to failures in factors involved in DNA replication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Therefore, 77% (10/13) of the dMMR may contain the substitution of MSH6 with MSH3 or the substitution of MLH3/PMS1 with PMS2, which could, at least partially, explain the contradictory results of dMMR and MSI assays. Kupka et al (2008) increased the MSI-L detection rate by 9% using an expanded panel of reference loci including D2S443, Fluorescent PCR-capillary electrophoresis is a gold standard to detect microsatellite instability (Zhang and Li, 2013). Using this method, we found that PPGL is largely in the microsatellite stable state (MSS), which echoes the TMB levels previously reported in PPGL (Fishbein and Wilkerson, 2018).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Therefore, 77% (10/13) of the dMMR may contain the substitution of MSH6 with MSH3 or the substitution of MLH3/PMS1 with PMS2, which could, at least partially, explain the contradictory results of dMMR and MSI assays. Kupka et al (2008) increased the MSI-L detection rate by 9% using an expanded panel of reference loci including D2S443, Fluorescent PCR-capillary electrophoresis is a gold standard to detect microsatellite instability (Zhang and Li, 2013). Using this method, we found that PPGL is largely in the microsatellite stable state (MSS), which echoes the TMB levels previously reported in PPGL (Fishbein and Wilkerson, 2018).…”
Section: Discussionsupporting
confidence: 62%
“… Kupka et al (2008) increased the MSI-L detection rate by 9% using an expanded panel of reference loci including D2S443, D21S1436, D1S104, D3S1284, D16S752, and D11S1338, suggesting that detection of Bat25, Bat26, D2S123, D5S346, D17S250, and MONO-27 loci may not fully reflect the MSI status of PPGL. Thus, it is worthwhile to expand the microsatellite reference loci to improve the detection accuracy of MSI-H in PPGL.…”
Section: Discussionmentioning
confidence: 96%
“…In a small study of 22 pheochromocytomas (Kupka et al , 2008), 2 patients demonstrated MSI in 1 and 2 of three tetranucleotide repeats (D2S443, D16S752 and D21S1436) investigated; both cancers were defined as MSI-L by the Bethesda panel. None of the endocrine tumours in that study exhibited instability in the tetranucleotide markers used, although 13% were classified as MSI-H (Kupka et al , 2008). …”
Section: Prevalence and Relevance Of Emast In Human Cancersmentioning
confidence: 99%
“…Microsatellite analysis was performed applying an extended marker panel for endocrine tumors which was previously established in our department [9]. In brief, markers BAT25, BAT26, D2S123, and D17S250 were amplified in a multiplex PCR (multiplex 1) using the QIAGEN Multiplex PCR Master Mix (Qiagen) under following conditions: final concentration of each forward primer (dye labeled) was 0.2 μM, of each reverse primer 1 μM, DNA concentration was 100 ng.…”
Section: Methodsmentioning
confidence: 99%